MANAJEMEN/PENGELOLAAN SAMPAH MEDIS RUMAH SAKIT TENTARA BHAKTI WIRA TAMTAMA DI KOTA SEMARANG (STUDI MANAJEMEN LINGKUNGAN) - Lina Fitriyanti; Ida Hayu Dwimawanti; Aloysius Rengga (Journal of Public Policy and Management Review, 2013)
Management / waste management is not only achieved through decision - making, but by increasing the ability of the apparatus in providing a variety of materials on waste management through education and training - training on various structural performance of public services is not enough to simply done using indicators - indicators attached to it's own waste management as waste management procedures The study was conducted to determine how the waste management Bhakti Wira Tamtama Hospital Semarang city enlisted as measured by several indicators of management / waste management, namely: Planning, Organizing, Leading and Controlling.In addition, this study also conducted to determine the limiting factor of the medical waste management at Army Hospital Bhakti Wira Tamtama. This study used descriptive qualitative approach to data collection obtained from observations and interviews.The studies results showed that the management / waste management in the hospital enlisted Bhakti Wira which still can be seen from the maximum, the lack of quality human resources, facilities and inadequate infrastructure, lack of attention and response to the civil servant leader. Researchers suggested that Wira Bhakti Hospital enlisted improve employee performance by conducting training for employees, adding facilities and infrastructure as well as improving medical waste management procedures.